Modeling of Electric Field Strength Around High Voltage Overhead Line - Balametov , A.B. (Herald of Azerbaijan Engineering Academy, 2025)
Calculation of line dimensions largely determines its design features during design. Electromagnetic field has a negative impact on the correct operation of communication lines and high-frequency electrical appliances, as well as human health and the state of the environment. Research conducted by physiologists prove the harmful effects of low-frequency electromagnetic fields on all living organisms and plants. The danger is confirmed by sanitary and hygienic standards for maximum permissible levels of electric and magnetic fields of industrial frequency for zones of various purposes, as well as by limiting the time of personnel stay in the zone with electromagnetic radiation. Determining the exact values of electric and magnetic field strengths allows developing a full set of measures to mitigate their harmful effects on humans and objects of the bio- and technosphere. A method for calculating the electric field at a distance from a highvoltage overhead power line has been developed. The calculation results are demonstrated using the example of a 500 kV power line depending on the overall dimensions.